Merkouris, Anastasios - (:unkn) unknown (My University, 2026)
Anastasios Merkouris is Associate Professor at the Department of Nursing, Cyprus University of Technology since 2008. He graduated from the Department of Nursing of the University of Athens and then acquired a Master’s degree (Msc) from the University of California San of Nursing Francisco (USA) and a PhD from the University of Athens in Nursing Management. He has worked for many years as Visiting Professor at the Military School of Nursing Officers, as Associate Professor and Chair of the Department of Nursing at the Higher Technological Institute (ATEI) of Crete and he has a lot of experience in health care professional training. He also has served in many special positions at the Cyprus University of Technology, as Chair and Vice Chair of the Department of Nursing, Dean of the school of Health Sciences, Member of the University Board, President of the Academic Union, Member of Senate committees etc. He is teaching Methodology of Research, Nursing Management, Quality Management of Health Services and Teaching Methodology in Nursing. His research interests focus in the Organization of nursing care, Nursing Leadership, Quality Management of Health Care Organizations, Patient satisfaction, Organizational culture, Health Related Quality of Life, Patients’ rights and Educational Assessment.
Keywords: nursing